SISTEM PENGENDALIAN INTERNAL, PARTISIPASI MASYARAKAT, MACHIAVELLIAN DAN PENGAWASAN BPD TERHADAP KECURANGAN DANA DESA DENGAN MORALITAS INDIVIDU SEBAGAI VARIABEL MODERASI - Rahmawati, Dina Fitri; Purnama, Dendi; Puspasari, Oktaviani Rita; Febriansyah, Yudi (Program Studi Akuntansi, Universitas Kuningan, 2023)
This study aims to determine the effect of the internal control system, community participation, Machiavellian and BPD supervision on village fund fraud with individual morality as a moderating variable in all villages in Cineam District, Mangunreja District and Tanjungjaya District, Tasikmalaya Regency. The method used in this research is descriptive method and verification method. The population obtained was 92 village fund management officers. The sampling technique used is a saturated sample where the entire population is sampled. The data analysis technique used is multiple linear regression analysis and moderated regression analysis. Based on the results of the study, it shows that the Internal Control System has a significant negative effect on Village Fund Fraud, Community Participation has a significant negative effect on Village Fund Fraud, Machiavellian has a significant positive effect on Village Fund Fraud, and BPD Supervision has a significant negative effect on Village Fund Fraud. Moderation regression analysis shows that Individual Morality moderates the Internal Control System Against Village Fund Fraud, Individual Morality moderates Community Participation Against Village Fund Fraud, Individual Morality does not moderate Machiavellian Against Village Fund Fraud, and Individual Morality moderates BPD Supervision of Village Fund Fraud. Keywords: Internal Co Control System, Community Participation, Machiavellian, BPD Supervision, Individual Morality, Village Fund Fraud.